ASSESSMENT OF KNOWLEDGE REGARDING KANGAROO MOTHER CARE AMONG NURSES OF A GENERAL HOSPITAL OF LAHORE - KAYNAT , C; SAOUL, A; SHEHZAD, H; ULLAH, K; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Kangaroo Mother Care (KMC) is a proven cost-effective intervention for managing preterm and low-birth-weight infants, particularly in resource-limited settings. Despite its benefits, KMC adoption remains inconsistent in Pakistan. Nurses play a pivotal role in its implementation, but their knowledge and attitudes toward KMC have not been extensively studied. Objective: To assess the knowledge, attitudes, and practices of nurses regarding KMC in a general hospital in Lahore. Methods: A cross-sectional study was conducted with 180 nurses using a structured questionnaire. The questionnaire assessed demographic characteristics, knowledge, attitudes, and practices related to KMC. Data were analyzed using SPSS version 25, employing descriptive and inferential statistics. Results: The study revealed moderate knowledge and confidence levels among nurses regarding KMC. While 43.9% of participants were confident in understanding the principles of KMC, only 41.2% were knowledgeable about proper positioning techniques. Confidence in educating caregivers was higher (48.3%), but only 37.3% strongly believed in KMC’s contribution to neonatal health. Perceived institutional support was deemed adequate by 45.6% of participants, while 37.8% were receptive to further training. Conclusion: Despite moderate awareness, significant gaps in technical knowledge and institutional support hinder the effective implementation of KMC. Targeted educational interventions and policy reforms are needed to enhance nurses' competencies and promote the adoption of KMC in healthcare settings in Pakistan.